Clinical Presentation of Uterine Fibroid and the Presence of Co-Existing Other Pathologies Like Endometriosis and Adenomyosis at Tertiary Care Centre - Kayastha, Bhagirathi; Shrestha, Buddhi Kumar; Pradhan, Alok (Journal of College of Medical Sciences-Nepal, 2025)
Background Uterine fibroids are slow growing, benign tumors that arise from smooth muscle cells of the uterus. Their growth depends on estrogen and progesterone. They can present with excessive vaginal bleeding leading to anemia, weakness and pain during menstrual period, pelvic pressure, bladder and bowel impairment leading to urinary retention, abdominal lump or reproductive dysfunction. Adenomyosis and endometriosis can co-occur with fibroid and share overlapping estrogen related pathophysiological mechanisms. Methods This cross-sectional study was conducted in Department of Obstetrics and Gynecology, College of Medical Sciences from March to August 2025. Ethical approval was obtained from the Institutional Review Committee (IRC) of College of Medical Sciences and Teaching Hospital. Using the convenience sampling method, 288 women were evaluated, and 116 women were confirmed to have fibroid uterus and hence enrolled in the study. Clinical presentations like abnormal uterine bleeding (AUB), anemia, abdominal lump, retention of urine and ultrasound (USG) findings of fibroid were recorded. Data was entered in Microsoft Excel 2016 and analyzed using SPSS version 16. Results The mean age was 43.22 years and 71.6% were multiparous. 66% women had abnormal uterine bleeding, 24.64% had anemia and 19.36% had abdominopelvic mass. 71.6% women underwent hysterectomy and 12.1% myomectomy. Postoperatively, 81.9% women had intramural fibroid while 9.7% and 12.6% women had endometriosis and adenomyosis along with fibroid respectively. Conclusions Fibroid uterus manifests throughout a woman`s life so it is important to be aware of signs and symptoms for timely recognition. The most common clinical features were abnormal uterine bleeding and anemia which had negative impact on women's life.